Impacts of ocean acidification on marine shelled molluscs - Gazeau, F; Parker, L M; Comeau, S; Gattuso, J P; O'Connor, W A; Martin, S; Pörtner, H O; Ross, P M (Marine Biology, 2013)
Over the next century, elevated quantities of atmospheric CO2 are expected to penetrate into the oceans, causing a reduction in pH (-0.3/-0.4 pH unit in the surface ocean) and in the concentration of carbonate ions (so-called ocean acidification). Of growing concern are the impacts that this will have on marine and estuarine organisms and ecosystems. Marine shelled molluscs, which colonized a large latitudinal gradient and can be found from intertidal to deep-sea habitats, are economically and ecologically important species providing essential ecosystem services including habitat structure for benthic organisms, water purification and a food source for other organisms. The effects of ocean acidification on the growth and shell production by juvenile and adult shelled molluscs are variable among species and even within the same species, precluding the drawing of a general picture. This is, however, not the case for pteropods, with all species tested so far, being negatively impacted by ocean acidification. The blood of shelled molluscs may exhibit lower pH with consequences for several physiological processes (e.g. respiration, excretion, etc.) and, in some cases, increased mortality in the long term. While fertilization may remain unaffected by elevated pCO2, embryonic and larval development will be highly sensitive with important reductions in size and decreased survival of larvae, increases in the number of abnormal larvae and an increase in the developmental time. There are big gaps in the current understanding of the biological consequences of an acidifying ocean on shelled molluscs. For instance, the natural variability of pH and the interactions of changes in the carbonate chemistry with changes in other environmental stressors such as increased temperature and changing salinity, the effects of species interactions, as well as the capacity of the organisms to acclimate and/or adapt to changing environmental conditions are poorly described. © 2013 Springer-Verlag Berlin Heidelberg.